2015
DOI: 10.1016/j.joca.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Immortalization and characterization of mouse temporomandibular joint disc cell clones with capacity for multi-lineage differentiation

Abstract: Objective Despite the importance of TMJ disc in normal function and disease, studying the responses of its cells has been complicated by the lack of adequate characterization of the cell subtypes. The purpose of our investigation was to immortalize, clone, characterize and determine the multi-lineage potential of mouse TMJ disc cells. Design Cells from 12-week-old female mice were cultured and immortalized by stable transfection with human telomerase reverse transcriptase. The immortalized cell clones were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…The collagen II is also expressed in TMJ disc cells ( Fig. 1B ), which is in consistent with previous studies 29 30 . We found that the expression of FGFR3 in TMJ disc cells was significantly down-regulated in Fgfr3 cKO mice ( Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The collagen II is also expressed in TMJ disc cells ( Fig. 1B ), which is in consistent with previous studies 29 30 . We found that the expression of FGFR3 in TMJ disc cells was significantly down-regulated in Fgfr3 cKO mice ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…Additionally, the TMJ disc, a specialized fibrocartilaginous tissue, is similar to the meniscus in knee joints. Both of the chondrocyte- and fibroblast-like cell clones was detected in the TMJ disc 29 . The collagen II is also expressed in TMJ disc cells ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Obviously, the last approach is associated with the risk of altering molecular profile of the cell and hindering the precise reflection of in vivo state [35,36]. Nevertheless, as our approach did not prevent the inevitable inhibition of in vitro cancer cells proliferation, we made an attempt to transduce primary cancer cells with well-known immortalizing genes– SV40LT [37], BMI-1 [38] and hEST2 [39]. None of the utilized genes significantly prolonged culture time, neither in breast nor in prostate cells.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 63-70% of the cells in the mature TMJ disc are the elongated spindle shaped fibroblast-like cells (called fibrochondrocytes) [5,26], and these cells primarily expressed the fibroblast-specific protein 1 (FSP1) [26]. Immunofluorescence staining revealed that the expression of fibrochondrocyte marker FSP1 appeared in the stretched BMSCs, but not in the control group ( Fig.…”
Section: The Expression Of Fibrochondrocyte Marker Was Enhancedmentioning
confidence: 98%